Communication and Community: The Community Service to Optimize for Computer Literacy and Internet Training for Bekasi Societies - Karim, Muhammad Firman; Riady, Yasir; Arisanty, Melisa; Majidah, Majidah; Riady, Hamdi; Hendrayana, Angga Sucitra (Syarif Hidayatullah State Islamic University of Jakarta, 2023)
Indonesia has a degree of literacy capacity; however, the reading interest in the community is still highly concerning; hence, the volunteer is required to increase information literacy and digital transformation so that the country can compete globally. Information literacy is one of the qualities necessary for a person to possess, particularly in today's world of intense international rivalry and rapid digital transformation. Information Literacy is required due to the rapid development of information so the need for information literacy is necessary. The most important reason is that everyone needs to recognize that there is a great deal of information circulating. This study aims to describe the implementation of community service in optimizing computer literacy and internet training for the Bekasi Society. This study used community-based research (CBR) as the method, particularly in advancing communication and information technology, which highly supports the dissemination of information to the public as a whole. The finding shows that there is an improvement in participants’ information literacy abilities and their capacity to use computers and the internet. All participants in the Community Service comprehended the methods to search for information via the internet, create and produce engaging learning materials, and use computers and current media to support the learning process.